Replicating & reproducing policing research - Monk, Khadija; Koziarski, Jacek (Routledge Taylor & Francis Group, 2024)
This book addresses the need for policing scholarship to strengthen its empirical cumulative knowledge base by replicating and reproducing earlier studies. It was originally published as a special issue of Police Practice and Research